2022
DOI: 10.28991/hij-2022-03-02-09
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis of Cryptocurrency using Business Intelligence Dashboard

Abstract: There are currently more than 10.000 cryptocurrencies available to buy from the online market, with a vast range of prices for each coin it sells. The fluctuation of each coin is affected by any social events or by several important companies or people behind it. The aim of this research is to compare three cryptocurrencies, which are Bitcoin, Ethereum, and Binance Coin, using Social Network Analysis (SNA) by visualizing them using Business Intelligence (BI Dashboard). This study uses the SNA parameters of deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Thus, the researchers used Harman's One Factor Test to examine the Common Method Bias (CMB). Findings revealed the CMB value at 16.7%, which is lower than the threshold value of 50% [44,52]. Results revealed that the current study's Common Method Bias (CMB) is under control.…”
Section: -2-common Methods Biasmentioning
confidence: 58%
“…Thus, the researchers used Harman's One Factor Test to examine the Common Method Bias (CMB). Findings revealed the CMB value at 16.7%, which is lower than the threshold value of 50% [44,52]. Results revealed that the current study's Common Method Bias (CMB) is under control.…”
Section: -2-common Methods Biasmentioning
confidence: 58%
“…In the recent past, many survey studies were written with a sole emphasis on cryptocurrencies [12][13][14] or simply consensus algorithms [15][16][17]. Smart contracts and the architecture of blockchain applications have been briefly explored in a few articles (e.g., [8].…”
Section: What This Survey Contributes and How It Compares To Other Su...mentioning
confidence: 99%
“…Salahuddin [26] states that Generation Y believes that hard work and goal setting help them achieve their dreams, that they personify tech savviness through social networking and constant connectivity, that they expect to have everyone's full attention and feedback, including mentoring and training, and that they require exciting and relevant work. Within this context, they are also entrepreneurial, while valuing work-life balance more than all previous generations [40][41][42].…”
Section: -3-generation Ymentioning
confidence: 99%
“…According to the heterogeneity of the workforce in terms of age, origin, education, religion, etc., their interests and expectations are shaping companies. By living and working together, different generations learn from each other and recognize the advantages of older or younger colleagues [39][40][41]. This cross-fertilization makes categorization difficult or even counterproductive, as employees feel like individuals and want to be treated as such.…”
Section: -Conclusionmentioning
confidence: 99%